Alteration of Musashi1 Intra-cellular Distribution During Regeneration Following Gentamicin-Induced Hair Cell Loss in the Guinea Pig Crista Ampullaris - Kinoshita, Makoto; Fujimoto, Chisato; Iwasaki, Shinichi; Kashio, Akinori; Kikkawa, Yayoi S.; Kondo, Kenji; Okano, Hideyuki; Yamasoba, Tatsuya (Frontiers in Cellular Neuroscience, 2019)
The mechanism underlying hair cell (HC) regeneration in the mammalian inner ear is still under debate. Understanding what molecules regulate the HC regeneration in mature mammals will be the key to the treatment of the inner ear disorder. Musashi1 (MSI1) is an RNA binding protein associated with asymmetric division and maintainance of stem cell function as a modulator of the Notch-1 signaling pathway. In this study, we investigated the cellular proliferative activity and changes in spatiotemporal pattern of MSI1 expression in the gentamicin (GM)-treated crista ampullaris (CA) in guinea pigs. Although the vestibular HCs in the CA almost disappeared at 14 days after injecting GM in the inner ear, the density of vestibular HCs spontaneously increased by up to 50% relative to controls at 56 days post-GM treatment (PT). The number of the type II HCs was significantly increased at 28 days PT relative to 14 days PT (p < 0.01) while that of type I HCs or supporting cells (SCs) did not change. The number of SCs did not change through the observational period. Administration of bromodeoxyuridine with the same GM treatment showed that the cell proliferation activity was high in SCs between 14 and 28 days PT. The changes in spatiotemporal patterns of MSI1 expression during spontaneous HC regeneration following GM treatment showed that MSI1-immunoreactivity was diffusely spread into the cytoplasm of the SCs during 7-21 days PT whereas the expression of MSI1 was confined to the nucleus of SCs in the other period. The MSI1/MYO7A double-positive cells were observed at 21 days PT. These results suggest that regeneration of vestibular HCs might originate in the asymmetric cell division and differentiation of SCs and that MSI1 might be involved in controlling the process of vestibular HC regeneration.